WHERE TO LOCATE HEART, MIND AND ME MYSELF? (LIFE CONTROVERSIES OF TWO WILLS OF NATALIA KOBRYNSKA) - Shvets А. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
On the basis of archival and memoir materials the article highlights the history of the two versions of wills of Natalia Kobrynska 1914 and 1920, as well as associated with it legal and personal psychological collisions that accompanied the process. The time from one testament to the other was marked by difficult life challenges for the writer (military events, human loneliness, failure and break with her society in Lviv, awareness of the tragedy of lost motherhood) which influenced the content of her last will, forcing in hard internal struggles and split to determine in favor of the family or community. Separately it highlights the dramatic history of testament per-formance of Kobrynska by her heirs and the tragic fate of the lost intellectual heritage of hers. In the context of biography both wills are valuable not only as documents of property status and family inheritance of Kobrynska and Ozarkevych family, but as a distinct expression of psychospiritual state of the testator in the period of her life ending .